(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the frequency of hypotension after giving prophylactic intramuscular ephedrine and intramuscular phenylephrine in parturients undergoing elective caesarean-section in subarachnoid block. Study Design: Randomized Controlled Trial. Setting: Department of Anaesthesia, Sir Ganga Ram Hospital, Lahore. Subjects and methods: A total of 270 cases (135 in each group) were included in this study, group-A received intramuscular ephedrine and group-B received intramuscular phenylephrine. Results: Mean age was 26.15±5.27 and 26.53±5.23 in group-A and group-B, respectively. Frequency of hypotension in group-A was found to be 47 patients (34.8%) and in group-B frequency of hypotension was found to be 68 patients (50.4%). Difference was statistically significant between two groups (P=0.013). ASA-I status was in 77.8% and 74.0% in group-A and B, respectively. Similarly, ASA-II status was found in 22.2% patients of group-A and 26.0% of group-B. Conclusion: In conclusion, phenylephrine 4 mg i.m., and ephedrine 45 mg i.m., reduces the severity of hypotension during spinal anaesthesia for Caesarean section. However, in i.m. Phenylephrine (4mg) group was significantly effective in preventing hypotension when compared with i.m ephedrine (45mg) group.